ONTOLOGICAL ATAVISMS IN THE DOMESTIC OCCUPATIONAL MEDICINE IN THE DIAGNOSIS OF OCCUPATIONAL DISEASE AND ASSESSMENT OF OCCUPATIONAL RISK - Разумов, Владимир Валентинович (Medicine in Kuzbass, 2022)
In the domestic occupational pathology (medicine of labor) of the last decades, the ideas about professionally determined health disorders have undergone significant advances initiated by the reformatory innovations of the World Health Organization (WHO) and the International Labor Organization (ILO). However, in occupational pathology approaches, the fundamental concepts of occupational diseases, occupational risks, and diseases associated with work are actually based on the occupational pathology mentality of the middle of the last century; medical terminology sins with vagueness, understatement; ambiguity or inconsistency, which complicate the practical work of all links of occupational pathology support for workers in harmful working conditions. The substitution of medical criteria for assessing health disorders by social attitudes contradicts not only the molecular biological level of modern medical ontology, but also its level of morphological determinism, rooted in the time of R. Virkhov. Domestic occupational medicine urgently needs, not in words, but in practice, to harmonize with international standards of medical care for workers, which is the case in other sections of general pathology and clinical medicine, to which it belongs.